Prevention Behavior of Dengue Hemorrhagic Fever in Community Leaders in the Work Area of the Hajimena Health Center, South Lampung Regency - Lolita Sary; Agung Aji Perdana; Riyanti Riyanti; Aulyya Rahmah (Postgraduate, University of Mataram, 2023)
Dengue Hemorrhagic Fever is a disease that causes the hajimena health center to be included in the top 9 health centers with dengue endemic areas. In 2021, the Incidence rate (IR) is 45.29 per 100,000 residents. One of the causes of this disease is due to the lack of role of community leaders in preventing DHF. The purpose of this study was to determine the relationship between knowledge, attitudes, motivation and information sources of community leaders on DHF prevention behavior. This type of research is quantitative research with an analytic research design and a cross sectional approach. The sample is 67 community leaders with 7 hamlet heads and 60 RTs taken using total sampling technique. With analysis using the Chi – square test. This research was conducted in October–March 2023. The results of the univariate analysis showed good knowledge of 61.19%, positive attitude of 58.21%, high motivation of 53.73%. Verbal information sources at 56.72% and non-verbal information sources at 43.28%. The results of the bivariate analysis showed that there was a relationship between knowledge, attitudes, and motivation with DHF prevention behavior with p-values ​​(0.00), (0.00), and (0.00). There is no relationship between information sources and DHF prevention behavior (0.90). The need for the role of health workers to form a community or group of community leaders who are named or term